IMPLEMENTATION OF KANBAN APP ON BORNEO CELL USING GO PROGRAMMING LANGUAGE AND TAILWINDCSS - Ramadhan, Ilham; Hanum, Yuhilza (Universitas Gunadarma, 2024)
The development of information technology has changed business dynamics with the use of efficient project management systems. Borneo Cell Shop, as a retailer that sells gadgets and accessories, needs an effective task management system to optimize employee workflow and task priorities. This research implements the kanban method at the Borneo Cell shop in the form of an application for its operations. This research includes the stages of planning, design, development and testing. The UML diagrams used for the design are use case diagrams and activity diagrams. The navigation structure used is the composite (mixed) structure. Database was created with PostgreSQL, and consists of users, categories and tasks. The interface design is made using wireframes. The programming language and tools used are Go language and Tailwind CSS. This application provides the form for new users to register, and then create the record of email address and password in the existing database. Functions that are related to the workflow are creating/adding, moving, and deleting categories and tasks. There are also informative messages for the cases of wrong input. This research is similar to previous ones, but differ in the field of implementation and design details. Test results show that this application can function correctly and is ready to be used in Borneo Cell Shop.